Managing Bank Loans By Using Neural Networks - ramadan al-Brahimi; Nima Abdullah AL-Fakhry AL-Fakhry (Al-Rafidain Journal of Computer Sciences and Mathematics)
This study aims at recognizing the role of neural networks in deciding administrative decisions in banks. To achieve the aims, the study developed a suggested model that depends on artificial neural networks as a stabilization tool to support loans management decisions. The Descent Conjugate Gradient algorithm is adopted to build the suggested model through checking loan demands according to the various banking instructions. The results showed that using such techniques in administrative business was a success through evaluating loan demands and deciding the most appropriate ones, with the possibility of refusing or accepting the agent’s demand, and also the possibility of deciding the loans which were demanded more than the other types.